1999
DOI: 10.1074/jbc.274.14.9836
|View full text |Cite
|
Sign up to set email alerts
|

Photorhabdus luminescens W-14 Insecticidal Activity Consists of at Least Two Similar but Distinct Proteins

Abstract: Both the bacterium Photorhabdus luminescens alone and its symbiotic Photorhabdus-nematode complex are known to be highly pathogenic to insects. The nature of the insecticidal activity of Photorhabdus bacteria was investigated for its potential application as an insect control agent. It was found that in the fermentation broth of P. luminescens strain W-14, at least two proteins, toxin A and toxin B, independently contributed to the oral insecticidal activity against Southern corn rootworm. Purified toxin A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…From earlier studies, it has been suggested that class A proteins harbor the cytotoxic effects of the Tc toxins, whereas class B and C proteins modulate and enhance the toxicity of class A proteins (16). However, recently, we elucidated the molecular mechanism of the Photorhabdus luminescens Tc complex, which consists of the class A protein TcdA1, the class B protein TcdB2, and the class C protein TccC3 or TccC5 (17).…”
mentioning
confidence: 99%
“…From earlier studies, it has been suggested that class A proteins harbor the cytotoxic effects of the Tc toxins, whereas class B and C proteins modulate and enhance the toxicity of class A proteins (16). However, recently, we elucidated the molecular mechanism of the Photorhabdus luminescens Tc complex, which consists of the class A protein TcdA1, the class B protein TcdB2, and the class C protein TccC3 or TccC5 (17).…”
mentioning
confidence: 99%
“…Other toxin proteins isolated and characterized from bacteria related to Xenorhabdus are the Tc toxins from P. luminescens strain W14 (17)(18)(19), a 39-kDa toxin from X. nematophila (20), the large Xin toxin from X. nematophila strain BJ (21), and the PhlA hemolysin from P. luminescens strain TT01 (22). Of these, only the Tc toxins have been studied in any detail.…”
Section: Discussionmentioning
confidence: 99%
“…The PhlA hemolysin was shown not to be a major virulence determinant (22). The Tc toxins from P. luminescens W14 form a large protein complex that is toxic to insects by either ingestion or injection (17)(18)(19). The high molecular mass complex consists of about 10 polypeptides, ranging in size from 30 to 200 kDa, which is secreted from the bacteria and requires proteolytic processing for activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations